HLA-B27 is associated with reduced disease activity in axial spondyloarthritis - James T. Rosenbaum (Nature Portfolio, 2021)
Abstract HLA-B27 is associated with increased susceptibility and disease activity of ankylosing spondylitis, but the effect of HLA-B27 on the activity of the broader category now called axial spondyloarthritis (AxSpA) is apparently the opposite. A modified Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) was used to assess disease activity among 3435 patients with spondyloarthritis (SpA) who participated in a survey designed to assess the effect of their disease and its treatment on the susceptibility and severity of Covid-19. Chi square testing was used to compare BASDAI scores between HLA-B27 positive and negative subjects. 2836 survey respondents were HLA B27 positive. The average BASDAI for the HLA-B27 negative cohort was 4.92 compared to 4.34 for the HLA-B27 positive subjects. Based on linear regression, a subject’s sex could not fully account for the differing BASDAI score in HLA-B27 negative subjects compared to those who are HLA-B27 positive. The difference between B27 positive and negative subjects was skewed by those with a BASDAI score of one or two. HLA-B27 positive subjects were more than twice as likely to have a BASDAI score of 1 compared to HLA B27 negative subjects and about 60% more likely to have a BASDAI score of 2 (p < 0.0001). HLA-B27 positive subjects have less active spondyloarthritis compared to HLA-B27 negative subjects as measured by a BASDAI score. Our data indicate that patients with mild back pain and a diagnosis of AxSpA are disproportionately HLA-B27 positive. The HLA-B27 test facilitates the diagnosis of axial spondyloarthritis such that patients from a community survey with mild back pain may be disproportionately diagnosed as having AxSpA if they are HLA-B27 positive. The test result likely introduces a cognitive bias into medical decision making and could explain our observations.